IPMS sponsors agricultural value chain exhibition in Ethiopia - Hoekstra, Dirk (International Livestock Research Institute, 2011)
On March 31, 2011, IPMS and the Oromia Bureau of Agriculture organized an exhibition of Agricultural Value Chains. In this video, Dirk Hoekstra (ILRI) introduces the exhibition and its relevance.